Old Stage Road - Kjysten Drew:::Creator::::::::::::
Old Stage Road, from which Cal and Abra gather azaleas in East of Eden, though there are no azaleas in this area. 'It was the end of May before the Silacci boys brought the news that the salmon pink blossoms of the azaleas were breaking free....It's a pleasant little stream that gurgles through the Alisal against the Gabilan Mountains on the east of the Salinas Valley' (762-63). Original is slide.